Analisis Perspektif Gender dalam Strategi Coping Anak Usia Dini - Farantika, Dessy; Rachmah , Laela Lutfiana; Purwaningrum, Devia; Sulistiyani Sanjaya, Maulinda (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
Children's interactions are often faced with various problems, and the ability to cope with these problems is fundamental for children to have. Coping strategies become a tool that can be applied for children to deal with various situations, both external and internal problems. In this study, the subjects consisted of one teacher, two parents, and two students. Data collection was conducted through interviews, observations, and documentation, using a qualitative research method approach. Qualitative research was chosen because researchers wanted to explore differences in coping strategies used by boys and girls when facing social and emotional problems. Data analysis was conducted using Miles and Huberman's interactive data analysis model, which involves several stages such as data collection, data reduction, data presentation, conclusion drawing, and verification. The results showed that children have been able to report various coping strategies, including seeking support, problem solving, distraction, and escape. Girls tended to be more dominant in seeking support than boys. In addition, coping responses with aggressive and destructive behaviors were more often found in boys than girls.